The demographics of consumer decision-making style dimensions in FMCG purchases - Saleh, Rosli; Tan, Boon See (Malaysian Consumer and Family Economics Association, 2002)
The study objective is to examine the relationships between demographic characteristics and the Malaysian consumer decision-making styles dimensions in Fast Moving Consumer Goods (FMCG) purchases. It is based on the modified Sproles and Kendall's (1986), Consumer Style Inventory (CSI) scale on 506 samples collected from the general public residing in the Klang Valley area. Using exploratory factor analysis, the findings indicate that there are between group differences as well as within group similarities in the consumers decision-making styles related to different demographic characteristics. This indicates the existence of demographic effects on consumers decision-making styles.